Quantifying the impact of a teamwork publication. Issue 4 (November 2021) - Cui, Haochuan; Zeng, An; Fan, Ying; Di, Zengru
Highlights: We find that paper impact is associated with the intrinsic ability of all authors of this paper instead of a single author. We propose a mathematical framework that can take into account co-authors' information when quantifying the impact of teamwork publication. Our model outperforms the existing methods in estimating the long-term impact of the teamwork publication. The contribution of each author to a paper can be obtained by fitting our model with real data. Abstract: We are now in the team explosion era, with an increasing number of scholars who choose to work in teams. Collaboration helps scholars increase productivity and the number of citations received. In the literature, there is a series of works aimed at understanding the impact of papers based on career data of individual researchers. A surprising finding is that the impact of the next paper that a researcher publishes is only determined by the intrinsic ability of the researcher and luck. However, this method neglects the effect of teamwork on the impact of papers, which may lead to contradictory predictions of a paper's impact if the predictions are made based on different co-authors. In this paper, we collect 481, 768 scientific articles published by the American Physical Society and analyse the collaboration behaviours of 236, 884 physicists. We propose a method to quantify the impact of teamwork. Given the information of team members, the study shows good performance in estimating the long-term impact of teamwork publications. This method also reveals the collaboration patterns in the careers of scholars to decode the complexity of collaboration dynamics.